2017
DOI: 10.1001/jamasurg.2017.0005
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities and Triple-Negative Breast Cancer in African American Women

Abstract: Oncologic anthropology represents a transdisciplinary field of research that can combine the expertise of population geneticists, multispecialty oncologists, molecular epidemiologists, and behavioral scientists to eliminate breast cancer disparities related to racial/ethnic identity and advance knowledge related to the pathogenesis of triple-negative breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
215
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(229 citation statements)
references
References 73 publications
11
215
1
2
Order By: Relevance
“…It has been known for a number of decades that black patients with breast cancer in the United States have a higher population-based breast cancer mortality than white patients. [34, 35] This is not fully understood but may relate to differences in socio-economic access to care, genetic and lifestyle factors as well as a propensity to develop an aggressive breast cancer subtype (triple-negative breast cancer). When adjusted for age only due to the small number of events in an exploratory analysis, our data indeed indicated that black patients had significantly worse OS compared to white patients (results not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for a number of decades that black patients with breast cancer in the United States have a higher population-based breast cancer mortality than white patients. [34, 35] This is not fully understood but may relate to differences in socio-economic access to care, genetic and lifestyle factors as well as a propensity to develop an aggressive breast cancer subtype (triple-negative breast cancer). When adjusted for age only due to the small number of events in an exploratory analysis, our data indeed indicated that black patients had significantly worse OS compared to white patients (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies with larger patient cohorts could help determine better the association between development of cardiotoxicity and breast cancer outcomes in black patients. [34]…”
Section: Discussionmentioning
confidence: 99%
“…For example, although overall rates of HR‐negative/HER2‐positive breast cancers in API women are similar to the rates in other groups, an analysis of California women by Asian ethnic subgroup reported that Korean, Filipina, Chinese, and Southeast Asian women had a higher risk of HR‐negative/HER2‐positive breast cancers compared with NHW women, whereas Japanese and American Indian women had lower risk for this subtype . Racial and ethnic differences in breast cancer subtypes may reflect variation in the prevalence of breast cancer risk factors, particularly reproductive factors, which are most strongly associated with HR‐positive breast cancers but also appear to reflect ancestry‐related genetic variations …”
Section: Selected Findingsmentioning
confidence: 98%
“…For example, diabetes is more common in blacks than in other racial/ethnic groups and is associated with an increased risk of cancer death . In addition, some cancer‐associated genetic mutations and aggressive tumor characteristics are more common among persons of African ancestry, and likely contribute to racial disparities for some cancers . The underrepresentation of blacks and other racial/ethnic minorities in clinical trials may exacerbate survival disparities by limiting knowledge about the efficacy of therapeutic agents in diverse populations .…”
Section: Selected Findingsmentioning
confidence: 99%